Whither Arab Women? The Arab Feminist Legacy and The Role of Women in The Arab Spring - Maheep Maheep; Yahya Jahanghiri (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The problem with the western line of thinking is that it makes a hasty assumption that religion naturally impedes social change. This assumption betrays the lack of a sense of cultural relativism and fails to comprehend the complex relationship between religion and society in West Asia and North Africa. In fact, Arab feminists recognized this truth a long time ago. As we illustrated above, Arab feminism began as a secular movement that viewed religion as a tool of oppression. It gradually revised its philosophy and reconciled its ideas with Islamic tenets. Scholars like Deniz Kandiyoti, Fatima Mernissi, and many Arab scholars vitally contributed to bringing this about. The Quran and the Hadiths are replete with the message of gender equality, so also the history of Islam which presents a very positive picture of gender relations. Scholars like Nikkie Keddie and Elizabeth Fernea have studied several different Arabic-speaking tribes and communities distributed from the Maghreb to the Arab Gulf. Their effort has revealed that from the historical past women in the Arab world have played significant roles in politics, legal institutions, administration, and even warfare. Therefore, we would like to express our reservations on apprehensions and anxieties which are so vociferously articulated by western academia and media during the developments following the Arab Spring in Tunisia, Egypt, Yemen, and other Arab states.